(3GdefgL GdoefJNH Edi CUhd ZQjH GdePgHs - (3Ydj Hf MGJe Hf eMeO GdJLjHj GdeZQHj, CHh GdMSf,J (B912 (3g` s
(3ChdgG (B:s
(3hHYO aGdZQV CVY Ydi GdefgL GdoefJNH Edi bhGYO GdePgH s
(3BNQgG (B:s
(3GdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde JSdjekG hdG Mhd hdGbhI EdG HGddg GdYdj GdYXje s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B593s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3MGdI GdfSNI LjOI s
Keywords: (3Gdabg GdeGdcjs